Penerapan Laravel Filament untuk Meningkatkan Sistem Manajemen Billing di Telkom Indonesia - Muhammad Sovian; Basworo Ardi Pramono (Jurnal Teknologi Terpadu, 2025)
Telkom Indonesia is a state-owned enterprise operating in the fields of information technology, communication, and telecommunication networks. Currently, Telkom faces challenges in managing financial data for its billing unit, which still relies on manual spreadsheets. This process takes approximately 65 to 80 minutes for 10 data entries and is prone to errors. Previous research using the waterfall methodology was found to lack flexibility in accommodating changing requirements. Therefore, this study developed a web-based application using Laravel and Filament, following the Agile methodology. The purpose of this development is to automate data management, enhance role-based security, and simplify report generation. Testing results show that the application improved data processing efficiency by 76%, achieved a 97% success rate in website performance testing, and produced more structured financial reports. Thus, the implementation of Laravel Filament has proven to be effective in enhancing operational efficiency and reducing data errors at PT Telkom Indonesia.